CEL-Seq2: sensitive highly-multiplexed single-cell RNA-Seq. Issue 1 (December 2016) - Hashimshony, Tamar; Senderovich, Naftalie; Avital, Gal; Klochendler, Agnes; de Leeuw, Yaron; Anavy, Leon; Gennert, Dave; Li, Shuqiang; Livak, Kenneth; Rozenblatt-Rosen, Orit; Dor, Yuval; Regev, Aviv; et al.
Abstract Single-cell transcriptomics requires a method that is sensitive, accurate, and reproducible. Here, we present CEL-Seq2, a modified version of our CEL-Seq method, with threefold higher sensitivity, lower costs, and less hands-on time. We implemented CEL-Seq2 on Fluidigm's C1 system, providing its first single-cell, on-chip barcoding method, and we detected gene expression changes accompanying the progression through the cell cycle in mouse fibroblast cells. We also compare with Smart-Seq to demonstrate CEL-Seq2's increased sensitivity relative to other available methods. Collectively, the improvements make CEL-Seq2 uniquely suited to single-cell RNA-Seq analysis in terms of economics, resolution, and ease of use.